New Methods of Special Education - Uusiautti, Satu; Määttä, Kaarina (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2018)
This book introduces research and solutions tested in schools with students with intellectual disabilities, socio-emotional difficulties, and extreme illnesses. It also provides extremely talented students' opinions on best teaching practices. In addition to students, the authors aim to bring out voices of their parents, teachers, and other people supporting them. The book serves people working with questions of special education: practitioners, researchers, and teachers and students in the field of special education worldwide. The authors present successful study processes which are secured by caring interaction, flexible, and student-centered teaching and multi-professional collaboration. The elements of caring education are the guiding principles of new special education.